PENGARUH KECEMASAN MATEMATIKA DAN KEMANDIRIAN BELAJAR TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMP NEGERI 5 PRAYA TAHUN AJARAN 2023/2024 - Arianti, Ria; Hikmah , Nurul; Kertiyani, Ni; Azmi, Syahrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of self-regulated learning on mathematical communication ability, the effect of mathematics anxiety on mathematical communication ability, and the effect of self-regulated learning and mathematics anxiety on mathematical communication ability. This research is included in quantitative research with an ex post facto type of research. The population in this study was 80 students with a sample size of 45 students taken using a simple random sampling technique. The instruments in this research were a mathematics anxiety questionnaire, a self-regulated learning questionnaire and a mathematical communication ability test. The results of this research show that 1) there is a significant influence between mathematics anxiety on the mathematical communication skills of class VIII students at SMP Negeri 5 Praya with a variable coefficient of -1.548 and a contribution value of 18.5%; 2) there is a significant influence between self-regulated learning on the mathematical communication skills of class VIII students at SMP Negeri 5 Praya with a variable coefficient of 0.971 and a contribution value of 20.6%; 3) there is a significant influence between mathematics anxiety and self-regulated learning on the mathematical communication abilities of class VIII students at SMP Negeri 5 Praya with a variable coefficient for mathematics anxiety of -1.084 and self-regulated learning of 0.726 and a contribution value of 28.3%. Therefore, it is hoped that teachers can implement learning strategies focusing on managing mathematics anxiety and fostering self-regulated learning in students to enhance their mathematical communication abilities.